Benthos Diversity as a Water Quality Indicator of Coastal Waters Klumpang Beach, Labuan Bajo, East Nusa Tenggara, Indonesia - Muhammad Abdus Salam Jawwad; M R A Maulana; R H A Murti (BIOMEJ, 2021)
Indonesia as an archipelagic country has a very high wealth of aquatic resources with the level of diversity of aquatic ecosystems as the role of living organisms. Benthos is an organism that lives on the bottom sediment of a body of water. This organism lives relatively sedentary and cannot avoid contact with pollutants and its lifespan is relatively long, so that if there is a change in water quality and the substrate in which it lives, it will affect its composition and abundance. The purpose of this study was to determine the index of benthos diversity found in coastal waters. Klumpang, Labuan Bajo, East Nusa Tenggara, Indonesia. Therefore, benthos can be used as a bioindicator in observing pollution in water, especially on the Klumpang coast. The result shows that   Klumpang beach shoreline has a medium diversity index, adequate productivity level, balanced ecosystem, and medium ecological pressure. The three sampling points has Shannon-Wiener diversity index by 1.790, 1.589, and 1.309 by sequence. The unbalanced species distribution of the species may indicate an unstable ecosystem in the shoreline, as the impact of surrounding activities especially in the eastern side of the coast.